UTILIZATION OF DIGITAL MARKETING AS A MODERN TEBE AND PLASTIC EXCHANGE BRANDING STRATEGY IN PENEBEL VILLAGE - Sihaloho, Gloria Ayu Natalia; Putu Abiyasa, Agus; Rivaldo Purnama Berahi, Timoteus; Marchella Ernita Lestari, Ni Wayan; Timothy Ananda, Christian; Mella Saputri, Vivy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Garbage is still a problem in society. One of them is in Penebel Village itself. This can be seen from the low interest of the people of Penebel Village to separate organic and non-organic waste independently. Even though various efforts have been made by the Village to overcome the waste problem. Starting from providing education to the community to going directly to the field. There are several methods of processing waste carried out by Penebel Village, including processing organic waste by making modern tebe. Meanwhile, the processing of inorganic waste itself is carried out through a waste crematorium and also plastic exchange. Seeing the problem regarding waste that is still so large, one of the small groups, namely group 1, which is active in the village of Penebel, made a work program, namely branding. This work program was born as a form of solution from the Penebel Village Community Service Program students to influence public awareness about efforts to tackle the dangers of waste. For this reason, the branding carried out is modern Tebe branding and plastic exchange. From this community service activity, digital products have been produced in the form of branding videos about modern tebe and plastic exchange. In addition, this digital marketing activity has also been published on YouTube KKN Penebel Village